A Comparison of Characteristics and Outcomes of Opioid-Dependent Patients Initiating Office-Based Buprenorphine or Methadone Maintenance Treatment. Issue 2 (April 2014) - Fingerhood, Michael I.; King, Van L.; Brooner, Robert K.; Rastegar, Darius A.
Background: The purpose of this study was to compare demographic factors and 1-year treatment outcomes of patients treated with buprenorphine or methadone. Methods: The study included 252 subjects who received a prescription for buprenorphine in an academic internal medicine practice and 252 subjects who enrolled in a methadone maintenance program located on the same campus over the same time frame. Data were collected retrospectively. Patients were classified as "opioid-positive" or "opioid-negative" each month for a year based on urine drug testing and provider assessment. Successful treatment was defined as remaining in treatment after 1 year and achieving 6 or more opioid-negative months. Results: Buprenorphine patients were more likely to be male, have health insurance, be employed, abuse prescription opioids, and be human immunodeficiency virus (HIV) infected; they were less likely to abuse benzodiazepines. At 12 months, 140 (55.6%) of buprenorphine patients and 156 (61.9%) of methadone patients remained in treatment ( P =.148). Patients on methadone had a higher mean number of opioid-negative months (6.96 vs. 5.43; P <.001) and mean number of months in treatment (9.38 vs. 8.59; P <.001). On multivariable analysis, methadone maintenance was significantly associated with successful treatment (adjusted odds ratio: 2.10; 95% confidence interval: 1.43–3.07). Conclusions: Office-based buprenorphine and methadone maintenance programs serve very different populations. Both are effective, but patients on methadone had mildly better treatment outcomes.